Autopsy Study of Organ Weights in a Tertiary Care Centre in Kerala - Liza John; Krishnan B (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background : Organ weight and its morphometric parameters are one of the most important indicators ofpossible organ defects or diseases, therefore, many studies have evaluated the normal range of body andorgan morphometric parameters, such as organ size, weight, and volume, in different ethnic groups all overthe world. Weighing organs during Autopsy is not a mere physical exercise, but carries great medico legalsignificance.Methods: A retrospective study was conducted by the Department of Forensic medicine at Government TDMedical College Alappuzha from autopsy data collected between January 2013 and December 2018. A totalof 1206 cases (936 males and 270 females) were included in the study on the basis of inclusion criteria andthe findings were recorded in the pre-designed proforma and analyzed.Conclusions : The average age of patients was 46.81 (between the ages 18 and 98), males 46.68(betweenthe ages 18 and 95) and females 47.23 (between the ages 18 and 98). In Males, the average weight of thebrain was 1266.39g (between 700 and 1976g), right lung was 484.41g (between 110 and 1400g), left lungwas 425.09g (between 83 and 1426g), Heart was 289.56g (between 112 and 732g), Liver in male was1356.99g (between 116 and 2822g) , spleen in male was 107.79 (between 12 and 948g) , right kidney was119.53g (between 16 and 270g) and left kidney in male was127.16 (between 46 and 886g).In females the average weight of the brain was 1140.11g (between 725 and 1620g), right lung was 346.05g(between 98 and 992g), left lung was 303.43g (between 22 and 760g), was 241.13g between (68 and 479g);Liver was 1171.78g (between 550 and 2880g); spleen was 100.16g (between 18 and 509g); right kidney was101.91g (between 36 and 624g) and left kidney was 104.23g (between 20 and 234g).